Biogas enhancement in the anaerobic digestion of thermo-chemically pretreated sludge by stimulating direct interspecies electron transfer by biochar and graphene - Almegbl, Abdulaziz Mohammed; Munshi, Faris Mohammad A.; Khursheed, Anwar (Frontiers in Chemical Engineering, 2024)
It is necessary to pretreat waste-activated sludge (WAS) to disintegrate the sludge matrix and amend its anaerobic digestion (AD) with carbon-based materials (CMs) to accelerate direct interspecies electron transfer (DIET) in order to realize the maximum biogas potential of abundant and habitat-threatening organic WAS. The AD of WAS pretreated thermo-chemically at 0.5% NaOH (g/g dry sludge) and 125 °C microwave irradiation was amended by biochar doses of 0–40 g/L and graphene doses of 50–1,000 mg/L in the batch operation mode. Hybrid pretreatment of WAS deteriorated dewaterability but solubilized 38% of total chemical oxygen demand (COD). AD amended with 20 g/L biochar and 100 mg/L graphene had the optimum accumulative methane yield of 183.6 and 153.8 mL/gVS, respectively, which correspond to 42.8% and 24.8% increases compared to an unamended control assay with maximum methane content of 70.3% and 71.9%, respectively. The digestate of biochar- and graphene-amended assays resulted in higher TS% and alkalinity, reduced sCOD, VFA, and turbidity, and increased particle size distribution compared to control. Biochar-amended digestate had improved dewaterability, while digestate of graphene-amended assays resulted in worse dewaterability than control. The t-test showed a significant difference between the biochar and graphene amended batch assays, while principal component analysis (PCA) indicated that biogas yield was closely correlated with pH. CM-amended batch assays demonstrated superb fitting with modified Gompertz, logistic, and first-order models with a coefficient of determination above 0.97. Microbial community abundance and diversity were affected by CMs amendment, resulting in increased acetoclastic methanogen growth and transformed methanogenic metabolic pathways. An extended pilot-scale study and techno-economic and life cycle assessments are required to investigate environmental impacts and feasibility.